Fabrication, characterization and fibroblast proliferative activity of electrospun Achillea lycaonica-loaded nanofibrous mats - KABASAKAL, LEVENT; ÇAM, MUHAMMET EMİN; GÜNDÜZ, OĞUZHAN; TAŞKIN, TURGUT (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
The use of natural compounds such as biocompatible and non-toxic plant extracts, without undesired side effects, in tissue engineering applications, is highly preferred compared to chemical drugs. In this study, the characterization and performance of electrospun Achillea lycaonica-loaded (0.125, 0.250 and 0.500, wt%) poly (lactic acid) (PLA) (8%, w/v) nanofibrous mats for skin tissue engineering were investigated. SEM, FTIR, DSC, and tensile strength test of the electrospun nanofibers have been investigated. Drug releasing test and cell culture study were also carried out. Achillea lycaonica-loaded nanofibrous mats in 0.250 (wt%) and 0.500 (wt%) demonstrated excellent cell compatibility and increased the viability of NIH/3T3 (mouse embryo fibroblast) cells within 72 h. According to the results, Achillea lycaonica-loaded PLA nanofibers have proper tensile strength and controlled release. The working temperature range enlarged for the composites having higher plant extract content. Consequently, Achillea lycaonica-loaded nanofibrous mats have a great potential in skin tissue engineering applications.
Keywords: Electrospinning; Achillea lycaonica; Nanofibers; Polylactic acid; Fibroblast proliferation; Skin tissue engineering; INDOCYANINE GREEN; AQUEOUS EXTRACT; HEALING-PROCESS; ESSENTIAL OIL; ANTIOXIDANT; MILLEFOLIUM; YARROW